New proof of a combinatorial identity on stirling numbers of the second kind - Wang, Jun; Zhang, Caihuan (Utilitas Mathematica, 2009)
A new proof is presented for a combinatorial identity involving Stirling numbers of the second kind due to Grimaldi (2005).